Comparative Analysis of Dental Stem Cells from a Single Donor: Differences in Adipogenic Differentiation and Protein Profile - Marín-Uc, José A.; Aguilar-Hernández, Víctor; Hernández-Sotomayor, Teresa; Brito Argáez, Ligia; Nic-Can, Geovanny I.; Chuc-Gamboa, Martha Gabriela; Aguilar-Ayala, Fernando; Aguilar-Pérez, Fernando; Rodas-Junco, Beatriz A. (Odovtos - International Journal of Dental Sciences, 2024)
Dental stem cells (DSCs) are multipotent cells with high proliferation capacity and multilineage differentiation. Few studies have compared the cellular characteristics and adipogenic differentiation potential of DSCs derived from tissues of the same individual. The objective of this work was to evaluate the differences in growth characteristics, expression of mesenchymal stem cells (MSCs)-specific markers, and the proteomic profile in response to adipogenic differentiation, of dental pulp and periodontal ligament cells obtained from a single donor. Dental cells were isolated from the third molar of a single donor using the outgrowth method. To obtain the proliferation curve of the cells was evaluated by trypan blue analysis. After the cells were cultured in adipogenic medium, morphological changes were monitored by oil red O staining, as well as adipogenic markers PPARγ and adiponectin by RT-qPCR. Finally, a two-dimensional electrophoresis of the proteins isolated from these cells was performed to analyze the proteomic profile. The two types of DSCs share similar cellular characteristics; however, their capacity for adipogenic differentiation is different. Based on the protein profiling results, we identified five differentially expressed proteins between both types of stem cells. Our findings showed that dental pulp and periodontal ligament stem cells from a single donor have similar cellular characteristics but a different response to adipogenesis, which would explain the differences in the expression of their proteins.